Perspektif Hukum Islam terkait Larangan Menikah di Bulan Muharram bagi Masyarakat Jawa Desa Jati Mulyo - Zulpahmi Lubis; Mili Sahira Saragih; Irma Damayanti; Rhohis Kurniawan; Aidil Zihad; Nusaindah Nurul Amin; Rizky Akbar Muhaimin (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This research is a qualitative study which aims to find out the reasons for the prohibition on marriage in the month of Muharram for Javanese people and the views of Islamic law regarding this prohibition. The techniques used in this study are observation and interview techniques. The target population is the entire community of Jati Mulyo Village, Pegajahan District. However, there were only 2 subjects as the research sample. From the research results, it was found that the people in Jati Mulyo Village, Pegajahan District, Serdang Bedagai Regency still have great confidence in the customs that have been passed down from generation to generation regarding the prohibition of marriage in the month of Muharram. However, in the view of Islam there is no prohibition on getting married in that month. Precisely if we do the right and good worship in that month then we will get glory.